DESCRIPCIÓN CLÍNICA DE LA DEMODICOSIS BOVINA (Demodex bovis) EN CÓRDOBA, COLOMBIA - Cardona Á., José (2013)
A clinical description and diagnosis of bovine demodicosis was conducted in Cordoba, Colombia, through a descriptive and non-probabilistic study. Twelve crossbred calves of both sexes, 7 to 10 months of age with skin lesions compatible with bovine demodicosis were selected. Skin lesions consisted of severe disseminated nodular dermatitis, characterized by multifocal nodular appearance. Nodules were firm and of fibrous consistency with sizes between 3 mm and 1 cm in diameter, placed bilaterally in the neck and the back. The nodules contained caseous purulent material with presence of larvae and adult mites (Demodex bovis).